2023
DOI: 10.1177/17585732231155123
|View full text |Cite
|
Sign up to set email alerts
|

The 50 most-cited articles in reverse shoulder arthroplasty

Abstract: Background Citation analyses have been used to understand the impact that a group of publications has on its field. As the techniques and indications of reverse total shoulder arthroplasty (RTSA) continue to expand, it is important to identify articles that can orient readers to the history, evolution, and current status of the body of RTSA literature. The purpose of this study was to identify and analyze the 50 most-cited articles related to RTSA. Methods Various Boolean queries were searched on the Clarivate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 89 publications
1
6
0
Order By: Relevance
“…Of the included publications, only 3 were published in 2010 or before, with 2 of these papers originating from European authors (Mishra and Pavelko 2006;Randelli et al 2008;Everts et al 2008). The significant increases in the number of publications per year and prominence of American publications that was observed to occur in 2011 is consistent with other bibliographic analyses (Gross et al 2023). This geographical and chronological distribution suggests that the early development of PRP may have been more prominent in Europe while the use of PRP in musculoskeletal medicine within the United States did not catch on until after 2010.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Of the included publications, only 3 were published in 2010 or before, with 2 of these papers originating from European authors (Mishra and Pavelko 2006;Randelli et al 2008;Everts et al 2008). The significant increases in the number of publications per year and prominence of American publications that was observed to occur in 2011 is consistent with other bibliographic analyses (Gross et al 2023). This geographical and chronological distribution suggests that the early development of PRP may have been more prominent in Europe while the use of PRP in musculoskeletal medicine within the United States did not catch on until after 2010.…”
Section: Discussionsupporting
confidence: 79%
“…In this study, a majority (55%) of the publications were randomized controlled trials of Level I evidence, suggesting that the scientific community is relying upon the highest-quality evidence available to guide research and apply PRP in clinical practice. This elevated proportion of studies with high levels of evidence contrasts those found in other orthopedic bibliographic analyses investigating joint arthroplasties, in which many articles in the Top 50 are of Level III and Level IV evidence (Barbera et al 2020;Gross et al 2023). With both surgical and non-surgical applications, PRP, and other orthobiologics for that matter, may be ideal modalities for the conduction of randomized controlled trials that could have resulted in the rapid maturation of this body of literature comparted to largely invasive procedures such as arthroplasty.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations